2017
DOI: 10.1186/s12967-017-1172-1
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of protein purified derivative of Mycobacterium bovis

Abstract: BackgroundTuberculin skin test based on in vivo intradermal inoculation of purified protein derivative from Mycobacterium bovis (bPPD) is the diagnostic test for the control and surveillance of bovine tuberculosis (bTB).MethodsProteomic analysis was performed on different bPPD preparations from M. bovis, strain AN5. Proteins were precipitated from bPPD solutions by TCA precipitation. The proteome of bPPD preparations was investigated by bottom-up proteomics, which consisted in protein digestion and nano-LC–MS/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…Commercial A60 (S1 and S2) were subjected to shotgun proteomic analysis on LC-MS/MS and searched against BCG Uniprot database. Similar to previous studies of “method-antigen complexes” such as MTB and M. bovis PPD [38,39], shotgun proteomic analysis of the A60-BCG complex antigen preparation detected a high number of proteins, specifically 630 and 595 proteins with ≥2 significant matches in A60 S1 and A60 S2, respectively, of which 440 were common to both samples (71% of A60 S1; 74% of A60 S2), amounting to 778 combined protein matches (Figure 1A) (Table S1). Overall, the proteins identified in the A60 represents approximately 19.9% of the 3891 proteins identified in the BCG proteome [40].…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Commercial A60 (S1 and S2) were subjected to shotgun proteomic analysis on LC-MS/MS and searched against BCG Uniprot database. Similar to previous studies of “method-antigen complexes” such as MTB and M. bovis PPD [38,39], shotgun proteomic analysis of the A60-BCG complex antigen preparation detected a high number of proteins, specifically 630 and 595 proteins with ≥2 significant matches in A60 S1 and A60 S2, respectively, of which 440 were common to both samples (71% of A60 S1; 74% of A60 S2), amounting to 778 combined protein matches (Figure 1A) (Table S1). Overall, the proteins identified in the A60 represents approximately 19.9% of the 3891 proteins identified in the BCG proteome [40].…”
Section: Resultssupporting
confidence: 79%
“…However, in recent years, there have been emerging interest in re-evaluation of classical mycobacterial antigen preparations using global approaches such as mass spectrometry, which may provide more insights into their characteristics to inform research in biomarkers and vaccine development. These studies have primarily focussed on the proteomic profiling of PPD [38,39], a cocktail of antigens used for determining latent tuberculosis in the Tuberculin Skin/Mantoux Test (including M. bovis PPD, used for diagnosis of bovine TB), which has been historically purified from steaming cultures of MTB by repeated precipitation with ammonium sulfate [41]. Given the crude nature of the PPD and A60, it is unsurprising that the two preparations reportedly share several similar antigens [25].…”
Section: Discussionmentioning
confidence: 99%
“…2). Overall, all MBE field isolates clustered with M. bovis AN5 originally a Brazilian strain used to produce PPD worldwide 25,26 while the BCG-Like isolates clustered with Russian BCG strain which included the deletion of the RD1 region 19 (Supplemental Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The proteome analysis that was carried out by Santema et al [34], while using LC-MS/MS, showed that PPDs from the Netherlands and Spain share a high range of proteins with a high degree of homology, mainly between closely-related species as MAP and MA. Moreover, as reported by Roperto et al [64], proteome analysis of the PPDB using bottom-up proteomics (protein digestion and nano-LC-MS/MS analysis) showed 198 proteins, which had not already been reported, and the proteomic pattern overlapping 80 proteins with the previous proteomes of the UK and Brazil PPDBs and 139 protein constituents of the Korean PPDBs. When PPDJ, PPDA, and PPDB protein component is compared, specific regions can be identified in these not degraded proteins, which provide pathogen specific immune responses against specific etiologic agents, such as MAP, MA, and MB.…”
Section: Discussionmentioning
confidence: 61%